Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Dinas Kelurahan Cisaranten Bina Harapan - Rantau, Fawaz Malki; Agustriyana, Darwis (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
A civil servant must be able to provide the best service and do a good job, which can be measured by the performance produced. Good performance is performance that follows the rules that have been decided in order to achieve organisational targets. Workforce performance is influenced by a variety of factors, including friendship and the environment. Good performance criteria include having great motivation and great work discipline. The research aims to find out the effect of work motivation and work discipline on workforce performance in the Cisaranten Bina Harapan Village Office. The sample size for this study is 30 people. In this study, two techniques were used: the descriptive method and the verification method. The results of the study prove that work motivation has a positive but not significant effect on employee performance and that work discipline has a positive and significant effect on employee performance. According to the multiple linear regression equation, work motivation and work discipline both have an impact on employee performance.